Les espaces carcéraux au Moyen Âge - Charageat, Martine; Lusset, Elisabeth; Vivas , Mathieu (PrimaLun@, 2021)
While recent work has renewed our knowledge of execution sites and the internal layout of confinement places in the Middle Ages, the distribution of prison spaces and territories, and in particular the socio-spatial dynamics and logics of their location, have yet to be analyzed. These prison spaces are the subject of this book, written by historians, archaeologists and literary scholars. By prison space, we mean the space produced by one or more places of incarceration: the interior spaces of a prison in all their complexity and the exterior space, whether that of arrests, judicial executions or the immediate vicinity of the gaol. The fourteen essays deal with prison space at different scale (buildings, neighborhood, city or region) and use a wide variety of sources: judicial documents, urban regulations, prison rules, accounts, iconography, archaeological datas, literary texts, etc.